2009
DOI: 10.1177/1049732309350730
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas: The Experiences of Israeli Nurses

Abstract: In this study I explored ethical dilemmas in nursing to gain a better understanding of nurses' work and their professional status. Qualitative data on ethical dilemmas were collected by interviewing 52 nurses in 18 hospitals and health maintenance organizations. The transcribed interviews were analyzed using a stepwise method. Results indicate a large number of dilemmas that can be divided into five main categories: caring vs. following formal codes; fair process vs. fair outcome; organizational standards vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Some focused on nurses’ responses to ethical dilemmas or their thoughts related to ethical dilemmas. Several researchers sought to understand what led nurses to speak up (whistle‐blowing) to protect patients (Ahern & McDonald, ; Jackson et al., ; Shapira‐Lishchinsky, ). Ahern & McDonald () found that whistle‐blowers had a less traditional view of authority than those who remained silent; that is, whistle‐blowers did not automatically defer to persons in positions of authority.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some focused on nurses’ responses to ethical dilemmas or their thoughts related to ethical dilemmas. Several researchers sought to understand what led nurses to speak up (whistle‐blowing) to protect patients (Ahern & McDonald, ; Jackson et al., ; Shapira‐Lishchinsky, ). Ahern & McDonald () found that whistle‐blowers had a less traditional view of authority than those who remained silent; that is, whistle‐blowers did not automatically defer to persons in positions of authority.…”
Section: Resultsmentioning
confidence: 99%
“…Without collecting demographics, it is unclear if the participants had a larger presence in either practice setting, which is an important missing element to put the findings in proper context. Further, several qualitative researchers did not explain their recruitment strategies or address saturation (Chaves & Massarollo, ; de Carvalho & Lunardi, ; Eriksson et al., ; Shapira‐Lishchinsky, ), another limitation of the qualitative work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the nursing profession in Israel is currently in an ominous state: a substantial shortage of nurses is expected in the near future because too few people consider a nursing career and fewer qualified students are choosing nursing (Shapira‐Lishchinsky, 2009). According to health officials, Israel will have an 18% shortage of nurses by 2020, impairing the system's ability to provide quality health care (Rotem‐Picker & Toren, 2004; Shapira‐Lishchinsky, 2009). It is possible that the implementation of a new specialty in nursing could provide a novel venue, offering an integrative conceptual framework and training for the recruitment of potential new nursing students.…”
Section: Implications Of Forensic Nursing In Israelmentioning
confidence: 99%